Od odziva do pobude - Cerar, Aidan (Urbani izziv, 2014)
Participation in spatial planning has been studied extensively in the past decades, but many cases of spatial planning have nonetheless seen a gap between decision makers and local residents. This is why participation in spatial planning has become a classic research question of many urban planning-related sciences. The greatest focus has been on cases of participation that present some kind of reaction to plans or actions, whereas far less attention has been given to cases of participation based on initiatives and the search for new content for underused or decaying areas. Such cases usually start with initiatives for the new use of particular places and often result in physical changes to these places. This article defines various types of local initiatives, and it especially studies the distinction between reactionary and contributive local initiatives and relates them to the notion of community. The article is based on an analysis of two particular cases. The differences in these two cases represent a foundation for the article's conclusions, which emphasises the potentials for stimulating contributive participation. The conclusion includes recommendations for the spatial planning system to become more open to participation in terms of revitalising underused spaces because such space has been increasing during the economic downturn. The complex and inefficient system of spatial planning is turning away many creative initiatives.
Keywords: lokalne skupnosti; participacija; prostorsko urejanje; urbanism; urbanizem